Early evolutionary diversification of mandible morphology in the New World monkeys (Primate, Platyrrhini). Issue 113 (December 2017) - Rocatti, Guido; Aristide, Leandro; Rosenberger, Alfred L.; Perez, S. Ivan
Abstract: New World monkeys (order Primates) are an example of a major mammalian evolutionary radiation in the Americas, with a contentious fossil record. There is evidence of an early platyrrhine occupation of this continent by the Eocene–Oligocene transition, evolving in isolation from the Old World primates from then on, and developing extensive morphological and size variation. Previous studies postulated that the platyrrhine clade arose as a local version of the Simpsonian ecospace model, with an early phase involving a rapid increase in morphological and ecological diversity driven by selection and ecological opportunity, followed by a diversification rate that slowed due to niche-filling. Under this model, variation in extant platyrrhines, in particular anatomical complexes, may resemble patterns seen among middle–late Miocene (10–14 Ma) platyrrhines as a result of evolutionary stasis. Here we examine the mandible in this regard, which may be informative about the dietary and phylogenetic history of the New World monkeys. Specifically, we test the hypothesis that the Simpsonian ecospace model applies to the platyrrhine mandible through a geometric morphometric analysis of digital images of the jaws of extant and extinct species, and we compare these results to those obtained using a phylogenetic comparative approach based on extant species. The results show a marked phylogenetic structure in the mandibular morphology of platyrrhines. Principal component analyses highlight the morphological diversity among modern forms, and reveal a similar range of variation for the clade when fossil specimens are included. Disparity-Through-Time analysis shows that most of the shape variation between platyrrhines originated early in their evolution (between 20 and 15 Ma). Our results converge with previous studies of body mass, cranial shape, the brain and the basicranium to show that platyrrhine evolution might have been shaped by an early increase in morphological variation followed by a decelerated rate of diversification and evolutionary stasis.